Nâsikh Mansûkh Dan Implementasinya dalam Tafsir Al-Qur`an ul Majid An-Nūr Karya Muhammad Hasbi Ash-Shiddieqy - M. Irfanuddin; Abdul Muid N; Zakaria Husin Lubis (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The concept of naskh and mansukh is very important to understand the development of Islamic law. With the existence of texts, the last verses of the Qur'an that were revealed are considered more valid and replace the previous verses. This study aims to examine the concepts of naskh (cancellation) and mansukh (absolute cancellation) in Muhammad Hasbi Ash-Shiddieqy's Tafsir Al-Qur'anul Majid An-Nur, and identify their implementation in the interpretation of Al-Qur'anic verses. In his commentary, Ash-Shiddieqy identifies verses that are considered as texts and mansukh, and explains the relationship between these verses. The research method used is text analysis with a qualitative approach. The results of the study show that Muhammad Hasbi Ash-Shiddieqy paid considerable attention to the concepts of naskh and mansukh in his interpretations. He described how changes to law or shari'a provisions were carried out through texts and mansukh. Apart from that, Ash-Shiddieqy also gave an explanation of the purpose and wisdom behind the cancellation of these verses. These previous studies have related or intersected the same problem, but in a very different context. This research makes an important contribution in understanding Muhammad Hasbi Ash-Shiddieqy's view of the concept of naskh and mansukh in the interpretation of the Qur'an. These findings can provide better insight into how a contemporary scholar understands and applies the concepts of naskh and mansukh in the interpretation of the Qur'an.